Diesel Engine Combustion and Emission Characteristics of Polyoxymethylene Dimethyl Ether Blended with Biodiesel (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The use of biodiesel as an alternative fuel for diesel engines shows great potential. Polyoxymethylene dimethyl ether, also known as PODE, is frequently utilised as a fuel additive due to its high cetane number, low viscosity, and high oxygen concentration. During the course of this research, PODE is combined with biodiesel as a significant fuel component in order to enhance the low-temperature flow properties and viscosity of biodiesel. The objective of this study is to achieve superior engine emission characteristics and efficiency in comparison to the baseline operation that was carried out using neat diesel. Diesel (D100), biodiesel (B100), and biodiesel/PODE blend fuel (B85P15) will be used in the trials, and they will be carried out in a direct injection diesel engine while the engine is working under varying loads. The data on combustion, the amount of fuel consumed, and the emissions of gas are measured. The B85P15 model delivers the lowest soot emission, which is less than 0.01 grammes per kilowatt-hour, as well as the maximum combustion efficiency and the highest indicated thermal efficiency.